Low-loss and temperature stable (1-x)Ba3P2O8-xMg2B2O5 composite ceramics with low sintering temperature. Issue 5 (May 2023) - Fang, Zhen; Pang, Li-Xia; Zhou, Di; Wang, Xiao-Long; Ren, Sen; Liu, Wei-Guo
Abstract: In this study, the Ba3 P2 O8 and Mg2 B2 O5 were fabricated by the solid-state reaction method separately, and the (1-x)Ba3 P2 O8 -xMg2 B2 O5 (x = 0.2–0.4) low-temperature co-fired ceramic (LTCC) materials were obtained in the sintering temperature range of 880–960 °C. The phase compositions, microstructures, elemental compositions, and microwave dielectric properties of the (1-x)Ba3 P2 O8 -xMg2 B2 O5 composite ceramics were investigated by X-ray diffraction (XRD), scanning electron microscopy (SEM), energy-dispersive spectroscopy (EDS), and TE01δ mode dielectric resonator method, respectively. The results revealed that the Mg2 B2 O5 phase and Ba3 P2 O8 phase could coexist well in the (1-x)Ba3 P2 O8 -xMg2 B2 O5 composite ceramics without formation of any new phases. The abnormal grain growth of Ba3 P2 O8 grains was inhibited by the addition of Mg2 B2 O5 . In addition, through composition of Ba3 P2 O8 and Mg2 B2 O5, the temperature coefficient of resonant frequency (τf ) and quality factor (Q×f) were effectively optimized, and the sintering temperature was reduced to 880–960 °C. The optimal performance of 0.8Ba3 P2 O8 -0.2Mg2 B2 O5 composite ceramic was achieved at a sintering temperature of 920 °C, τf = −1.9 ppm/°C, Q×f = 61, 250 GHz, and a low permittivity εr = 10.7. The chemical compatibility test demonstrated that the composite ceramic could coexist well with silver, which indicated that the 0.8Ba3 P2 O8 -0.2Mg2 B2 O5 composite ceramic is a candidate LTCC material with wide application prospects.